The Effect of Devotional Worship and Spiritual Intelligence on Psychological Well-Being Students of Maitreyawira STAB - Yelly Selviana; Suherman Suherman; Partono Partono (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
The psychological well-being of students is increasingly getting a lot of attention from university and the community. From several studies, it was found that psychological well-being can affect academic achievement and also student’s success when entering the world of work and society. This study aims to determine the influence of worship and spiritual intelligence on the psychological well-being of STAB Maitreyawira Pekanbaru students. This study uses a quantitative method. The data collection technique was carried out by distributing questionnaires to 132 students of STAB Maitreyawira Pekanbaru. The sampling technique used was simple random sampling, with a sample of 102 students from various batches or different semesters. The data collection instrument was in the form of a closed questionnaire disseminated through google forms, the results of the questionnaire were tested through instrument testing, classical assumptions, simple and multiple regression correlation analysis. The results of the study showed that worship exerted an influence of 43.7%, spiritual intelligence was influential by 68%, while worship and spiritual intelligence simultaneously affected the psychological well-being of students by 69.5%. Therefore, it can be concluded that the psychological well-being of students can be improved through the implementation of devotional puja and increased spiritual intelligence.